Increasing incidence of ectopic pregnancy in one Norwegian county ‐ a population based study, 1970–1993 - Finn Egil Skjeldestad; Juliette S. Kendrick; Hani K. Atrash; Anne Kjersti Daltveit (Acta Obstetricia et Gynecologica Scandinavica)
Objective. To estimate time trends related to ectopic pregnancy while considering the contribution of repeat ectopic pregnancy and changing treatment for infertile couples over the past 24 years. Methods. Population based incidence data on ectopic pregnancy were collected from the only two hospitals in one Norwegian county from 1970 through 1993. Cases were identified through hospital discharge registries and all medical records were reviewed. Only females, aged 15‐44 years. living permanently in the county and having a histologically verified ectopic pregnancy were eligible for the study. Data were analyzed in 5‐year periods and 5‐year age‐groups. Results. The incidence of ectopic pregnancy (per 1,000 woman‐years) increased fourfold from the first to the last period. When we restricted the analyses to women with no previous ectopic pregnancy and n o previous infertility surgery or treatment, we observed a linear threefold increase in the number of ectopic pregnancies. Conclusions. Repeat ectopic pregnancy and increased infertility treatment in the late 1970s and early 1980s might explain at most 25% of the increase in the incidence of ectopic pregnancy. After 1985; assisted reproduction might contribute to 445%) of ectopic pregnancies diagnosed. The introduction of laparoscopy might explain some of this increase in the 1970s; however. we doubt that the introduction of more sensitive pregnancy tests or vaginal ultrasound in the 1980s contributed to the observed increase in ectopic pregnancy.